Sistem Informasi Pelayanan Jasa pada Lucky Photo - Pradita, T; Mubarok, A (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2021)
The development of services has developed into the internet media, to make it easier for customers and employees in managing a job. In the problem of Lucky Photo, which covers services including printing, sales, stock of goods, purchases, and reports are not effective properly. The researcher aims to develop a service system entitled Service Information Systems at Lucky Photo. By building a web-based application, a waterfall method is needed to become a benchmark for the creation of a service information system, so the results will be obtained on a web-based application system to demand progress in a company, including services that become easier, easier customer service in conduct transactions, generate reports, and process customer data. So it can be concluded that with the construction of a new Service Information System it will be easier to make transactions, make it easier for customers, create reports, and process customer data that is embedded in the Mysql database which will become a well-systemized report.